Strategi Pengembangan Pariwisata Berbasis Pertanian di Desa Pelaga Kecamatan Petang Kabupaten Badung - MAHENDRA, I PUTU MAYUN; PITANA, I GDE; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.1, Juli 2021, 2021)
Strategy for Developing Agriculture-Based Tourism in Pelaga Village, Petang District, Badung Regency This study aims to identify internal factors in terms of strengths and weaknesses as well as external factors, namely opportunities and threats using SWOT analysis method to determine strategies in developing agriculture-based tourism in Pelaga Village, Petang Sub-District, Badung Regency. Determination of key informants was done by purposive sampling technique. The data collection method was conducted using FGD (Focus Group Discussion) method .  The results of research show that strategies that can be carried out for the development of agriculture-based tourism in Pelaga Village, Petang Sub-District, Badung Regency are the Strengths-Opportunities strategies, namely developing agriculture-based tourism and maintaining various tourist attractions and promotion strategies. The Strengths-Threats Strategies can be done in two ways, namely the strategies of designing rules related to tourism areas and providing extension to the people of Pelaga Village. Weaknesses-Opportunities strategies that can be done is the arrangement of tourism locations. Weaknesses-Threats strategies that can be given are to provide tourism skills and knowledge training to the Pelaga Village community.